2022
DOI: 10.1002/eahr.500147
|View full text |Cite
|
Sign up to set email alerts
|

Participants’ Perspectives on Payment for Research Participation: A Qualitative Study

Abstract: Difficulty enrolling participants in randomized clinical trials (RCTs) is a recognized barrier to evaluating health interventions. 1 To overcome this barrier, many investigators offer payment to participants. Though widespread, this practice remains ethically contentious. 2 It has largely been debated on conceptual grounds, and concerns include that payment might unduly influence or coerce potential participants, undermining their informed consent, or result in the disproportionate enrollment of low-income or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…This was in line with other similar studies in Indonesia (Linawati et al, 2022). Although the practice of participation fees is widespread across the globe, it remains ethically contentious (Pollacsek, Boardman and McCann, 2017;Largent et al, 2022). However, according to Pollacsek, Boardman and McCann (2017), providing a payment as an incentive is not considered unethical as a payment is considered an offer rather than a threat.…”
Section: Payment Of Feessupporting
confidence: 87%
See 1 more Smart Citation
“…This was in line with other similar studies in Indonesia (Linawati et al, 2022). Although the practice of participation fees is widespread across the globe, it remains ethically contentious (Pollacsek, Boardman and McCann, 2017;Largent et al, 2022). However, according to Pollacsek, Boardman and McCann (2017), providing a payment as an incentive is not considered unethical as a payment is considered an offer rather than a threat.…”
Section: Payment Of Feessupporting
confidence: 87%
“…It is vital, however, that participants are provided with informed consent so they are aware of what they are agreeing to, being paid for and that the fees are equitable. According to Largent et al (2022), concerns about payments cited in other studies include that participation fees might unduly influence the participants or lead to coercion, undermine participant informed consent, or result in the disproportionate enrolment of low-income or otherwise disenfranchised individuals. However, their research, which was conducted in a developed country, found that incentives did not impact unduly on participant recruitment.…”
Section: Payment Of Feesmentioning
confidence: 99%
“…A meta-analysis of the effect of compensation on enrollment in randomized clinical trials showed that offering compensation significantly increased the rate of response and consent [ 7 ]. Additionally, other investigators have reported compensation as a motivating factor for participants, but not in a way that suggested undue influence or inducement [ 24 ]. The RETAIN study [ 25 ], led by investigators at the University of Pennsylvania, found that compensation significantly increased enrollment rates for a smoking cessation trial, but not for an ambulation intervention trial.…”
Section: Discussionmentioning
confidence: 99%